Fasting decreases plasma FGF21 in obese subjects and the expression of FGF21 receptors in adipose tissue in both lean and obese subjects. Issue 1 (October 2018) - Nygaard, Eva B; Ørskov, Cathrine; Almdal, Thomas; Vestergaard, Henrik; Andersen, Birgitte
Abstract : Fibroblast growth factor 21 (FGF21) is a metabolic regulator of energy and lipid metabolism. FGF21 is highly expressed in liver while FGF21 receptors (beta-klotho (KLB) and FGFR1c) are highly expressed in white adipose tissues (WATs). Plasma FGF21 has been shown to be increased after 7–10 days of fasting but oppositely plasma FGF21 is also increased in obesity. The aim of this study was to measure the effect of 60 h of fasting on plasma FGF21 levels in obese and lean subjects and to determine the gene expression of KLB and FGFR1c in the subcutaneous WAT before, during and after 60 h of fasting. Eight obese (BMI >30 kg/m 2 ) and seven lean subjects (BMI <25 kg/m 2 ) were fasted for 60 h and blood samples were taken at time 0 and after 12, 36 and 60 h of fasting. A biopsy from the subcutaneous WAT was taken at time 0, 12 and 60 h of fasting. FGF21 was measured in plasma by an ELISA and mRNA expression of KLB and FGFR1c was measured in WAT by quantitative PCR (qPCR). The fast significantly decreased plasma FGF21 in obese subjects while no change in plasma FGF21 was observed in lean subjects. Interestingly, KLB was significantly decreased in WAT in response to fasting in both lean and obese subjects indicating a potential important adaptive regulation of KLB in response to fasting.